Peroxidase-like material as well as preparation method and application thereof
Peroxidase-like materials are prepared by wrapping nano-precious metals with polymers and loading them on two-dimensional nanomaterials, which solves the problem of difficulty in detecting mercury ions in high-salt, high-acid, and high-oxidizing environments in the prior art, and achieves rapid, sensitive and specific mercury ion detection in such an environment.
Patent Information
- Application Number
- CN202510109890.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-05-09
AI Technical Summary
The prior art is difficult to effectively detect mercury ions in high-salt, high-acid, and highly oxidizing environments, and common detection methods are difficult to adapt to this environment.
Peroxidase-like materials are prepared by polymers wrapped in nano-precious metals and loaded on two-dimensional nanomaterials. This material has enhanced catalytic activity in a high-salt environment and can quickly, sensitively and specifically detect mercury ions.
In the neutralized nitric acid digestion solution, the catalytic activity of peroxidase-like materials is not only not reduced, but is also enhanced, and quantitative detection of mercury ions can be completed within 10 minutes, which has the advantages of high detection sensitivity, low detection limit and short time consumption.
Smart Images

Figure CN119951500A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanomaterials, and in particular to a peroxidase-like material and a preparation method and application thereof. Background Art
[0002] Mercury is highly toxic and a highly neurotoxin that is easily absorbed by the human skin, respiratory tract, and digestive tract. After entering the human body, mercury ions are slowly excreted from the body and mostly accumulate in the brain, damaging the central nervous system. They also have adverse effects on the mouth, mucous membranes, and teeth, causing symptoms such as slurred speech, facial dementia, hand and foot deformities, and even mental disorders. However, mercury is indispensable in the production and manufacturing of some chemical drugs, electronic appliances, catalysts, batteries, and other products. Mercury discharged into the environment is easily enriched in food and Chinese medicinal materials through the food chain and eventually ingested into the human body. Therefore, there is an urgent need for a fast and convenient mercury ion detection method to ensure the safety of food, medicine, and the environment.
[0003] In the pretreatment process of food, Chinese medicinal materials, etc., it is difficult to extract all mercury ions by only using steaming and organic solvent extraction methods. Nitric acid or nitric acid-hydrogen peroxide microwave digestion is an effective method for extracting mercury ions, which can digest all organic matter into inorganic ions. It is also the pretreatment method used in the heavy metal detection of the 2020 edition of the "Chinese Pharmacopoeia". However, the solution obtained after digestion contains a large amount of nitric acid, and its strong oxidizing property will destroy most of the detection probes. Even after neutralization, the highly concentrated salt solution can easily inactivate the detection probe, making it difficult to complete the detection. Although a large number of rapid mercury ion detection methods based on colorimetry, fluorescence, and electrochemical methods have been reported, these detection methods are difficult to adapt to the strong oxidation, high acid, and high salt environment of the digestion solution. Summary of the invention
[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the object of the present invention is to provide a peroxidase-like material, which uses a polymer to wrap a nano-precious metal and fix it on a two-dimensional nanomaterial, and the obtained peroxidase-like material has the characteristics of enhanced catalytic activity in a high-salt environment.
[0005] The second aspect of the present invention is to provide a method for preparing a peroxidase-like material.
[0006] The third aspect of the present invention is to provide a kit.
[0007] A fourth aspect of the present invention is to provide a method for detecting mercury ions.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] The first aspect of the present invention provides a peroxidase-like material, comprising a two-dimensional nanomaterial, a nano-precious metal and a polymer; the polymer wraps the nano-precious metal and is loaded on the two-dimensional nanomaterial; the two-dimensional nanomaterial has a wrinkled morphology.
[0010] The peroxidase-like material provided by the present invention adopts a two-dimensional nanomaterial with excellent specific surface area as a carrier, uses a high polymer with a large molecular weight as a stabilizer to wrap a nano noble metal, and is loaded on the wrinkled two-dimensional nanomaterial. The peroxidase-like material has peroxidase-like activity, and the catalytic activity in the neutralized nitric acid digestion solution not only does not decrease but is enhanced, and the activity is affected by the concentration of trace mercury ions. When hydrogen peroxide and a chromogenic substrate are present, the rapid, sensitive and specific quantification of mercury ions can be completed within only 10 minutes, and the method has the advantages of high detection sensitivity, low detection limit and short detection time.
[0011] In some embodiments of the present invention, the peroxidase-like material is in the shape of a crumpled paper ball.
[0012] It should be understood that in the peroxidase-like material, the polymer encapsulates the nano-precious metal and is loaded on the two-dimensional nanomaterial, so the crumpled paper ball shape of the peroxidase-like material is actually obtained by the two-dimensional nanomaterial being crumpled to form crumpled paper ball-like particles. After the two-dimensional nanomaterial is crumpled, it has better dispersibility and stability.
[0013] In some embodiments of the present invention, the particle size of the peroxidase-like material is 0.1-10 μm.
[0014] In some embodiments of the present invention, the particle size of the peroxidase-like material is 1 to 3 μm.
[0015] In some embodiments of the present invention, in the peroxidase-like material, the mass ratio of the nano noble metal to the polymer is (0.01-0.1):1.
[0016] In some embodiments of the present invention, the mass ratio of the nano noble metal to the polymer is (0.01-0.07):1.
[0017] In some specific embodiments of the present invention, the mass ratio of the nano noble metal to the polymer is (0.01-0.02):1.
[0018] In some embodiments of the present invention, in the peroxidase-like material, the mass ratio of the two-dimensional nanomaterial to the polymer is (0.01-0.4):1.
[0019] In some embodiments of the present invention, the mass ratio of the two-dimensional nanomaterial to the polymer is (0.01-0.08):1.
[0020] In the present invention, the composition ratio of the peroxidase-like material is calculated based on the ratio of the raw materials for preparing the peroxidase-like material, including two-dimensional nanomaterials, polymers and nano precious metal precursors, wherein the precious metal precursor includes at least one of chloroauric acid, silver nitrate, chloroplatinic acid and chloropalladic acid.
[0021] In some embodiments of the present invention, the two-dimensional nanomaterial includes at least one of graphene oxide and Mxene.
[0022] In some embodiments of the present invention, the graphene oxide can be prepared by the following method:
[0023] The concentrated sulfuric acid is cooled to below room temperature, and graphite and sodium nitrate are added in an ice bath, potassium permanganate is added after mixing, low-temperature reaction is carried out, and then the temperature is increased for medium-temperature reaction, and finally water is added to complete the high-temperature reaction; post-treatment is performed to obtain graphene oxide.
[0024] In some embodiments of the present invention, the post-treatment comprises the following steps: reducing unreacted potassium permanganate using H2O2, centrifuging, and washing multiple times.
[0025] In some specific embodiments of the present invention, the washing is performed by washing with 5-15% by mass hydrochloric acid for 3-5 times, and then washing with water until the supernatant is close to neutral.
[0026] In some embodiments of the present invention, the temperature of the low-temperature reaction is ≤20° C.; and the time of the low-temperature reaction is 20 to 40 minutes.
[0027] In some embodiments of the present invention, the temperature of the medium temperature reaction is 30-40° C.; the time of the medium temperature reaction is 60-120 min.
[0028] In some embodiments of the present invention, the temperature of the high temperature reaction is less than 100° C.; and the time of the high temperature reaction is 20 to 40 minutes.
[0029] The high temperature of the high-temperature reaction is actually the temperature of the system rising due to the presence of concentrated sulfuric acid in the reaction system after adding water. The temperature is controlled below 100°C to avoid splashing of water and concentrated sulfuric acid.
[0030] In some embodiments of the present invention, the amount of concentrated sulfuric acid is 5-23 mL; the amount of graphite is 0.25-1 g; the amount of sodium nitrate is 0.125-0.5 g; the amount of potassium permanganate is 0.75-3 g; and the amount of water is 10-50 mL.
[0031] In some embodiments of the present invention, the polymer includes at least one of xylan, chitosan, polyethylene glycol, and polyethyleneimine.
[0032] In some embodiments of the present invention, the nano precious metal includes at least one of gold, silver, platinum and palladium.
[0033] The second aspect of the present invention provides a method for preparing the peroxidase-like material according to the first aspect of the present invention, comprising the following steps:
[0034] The two-dimensional nanomaterial, the noble metal precursor and the polymer are mixed to form a mixture, and the enzyme material precursor is obtained by reaction;
[0035] The enzyme material precursor is mixed with an oil phase to react and obtain the peroxidase-like material.
[0036] In the preparation method of the present invention, the enzyme material precursor is actually also a structure in which a polymer encapsulates nano-precious metal and is loaded on a two-dimensional nano-material, but it is still a two-dimensional sheet structure. By further processing in the oil phase, the two-dimensional sheet is wrinkled to obtain a wrinkled paper ball structure.
[0037] In some embodiments of the present invention, the concentration of the two-dimensional nanomaterial in the mixture is 0.05-8 mg / mL.
[0038] In some embodiments of the present invention, the concentration of the two-dimensional nanomaterial in the mixture is 0.05-0.8 mg / mL.
[0039] In some specific embodiments of the present invention, the concentration of the two-dimensional nanomaterial in the mixture is 0.05-0.5 mg / mL.
[0040] In some embodiments of the present invention, in the mixture, the concentration of the noble metal precursor is 0.1 to 2 mmol / L.
[0041] In some embodiments of the present invention, in the mixture, the concentration of the noble metal precursor is 0.2-1 mmol / L.
[0042] In some embodiments of the present invention, in the mixture, the concentration of the polymer is 1 to 20 mg / mL.
[0043] In some embodiments of the present invention, in the mixture, the concentration of the polymer is 3-10 mg / mL.
[0044] It should be noted that the concentrations of the two-dimensional nanomaterials, the noble metal precursors and the polymer in the mixture are used for conversion to calculate the mass ratio relationship among the two-dimensional nanomaterials, the nano-noble metals and the polymer in the peroxidase-like material.
[0045] In some embodiments of the present invention, the mixture further comprises a reducing agent; the reducing agent comprises at least one of sodium citrate, ascorbic acid, and sodium borohydride.
[0046] In some embodiments of the present invention, in the mixture, the concentration of the reducing agent is 1 to 20 mmol / L.
[0047] In some embodiments of the present invention, in the mixture, the concentration of the reducing agent is 3-10 mmol / L.
[0048] In some embodiments of the present invention, the noble metal precursor includes at least one of chloroauric acid, silver nitrate, chloroplatinic acid, and chloropalladic acid.
[0049] In some embodiments of the present invention, the oil phase comprises at least one of plant oil and mineral oil.
[0050] In some embodiments of the present invention, the oil phase comprises at least one of olive oil, corn oil, coconut oil, palm oil, and paraffin oil.
[0051] In some embodiments of the present invention, the two-dimensional nanomaterial and the noble metal precursor are dispersed in water, heated to boiling, and then a reducing agent and a polymer are added to react to obtain the enzyme material precursor.
[0052] The reducing agent reduces the noble metal precursor to nano noble metal.
[0053] In some embodiments of the present invention, the reaction time of the mixture is 10 to 50 minutes.
[0054] In some embodiments of the present invention, the reaction time of the mixture is 10 to 40 minutes.
[0055] In some specific embodiments of the present invention, the reaction time of the mixture is 15 to 35 minutes.
[0056] In some embodiments of the present invention, the temperature of the oil phase is 130-190°C.
[0057] In some embodiments of the present invention, the temperature of the oil phase is 140-180°C.
[0058] In some specific embodiments of the present invention, the temperature of the oil phase is 150-170°C.
[0059] In some embodiments of the present invention, the volume of the oil phase is 50 to 200 mL.
[0060] In some embodiments of the present invention, the amount of the enzyme material precursor mixed with the oil phase is 5 to 50 mL.
[0061] In some embodiments of the present invention, the process of mixing the enzyme material precursor with the oil phase comprises the following steps:
[0062] The enzyme material precursor is added dropwise to the oil phase, and mixed by a homogenizer and / or magnetic stirring until there are no bubbles.
[0063] In some embodiments of the present invention, the speed of the homogenizer is 1000-3500 rpm.
[0064] In some embodiments of the present invention, the rotation speed of the magnetic stirring is 200-500 rpm.
[0065] In some embodiments of the present invention, after the enzyme material precursor is mixed with the oil phase for reaction, centrifugation and washing steps are also included.
[0066] The third aspect of the present invention provides a kit, comprising a peroxidase-like material and a color developing reagent; the peroxidase-like material is the peroxidase-like material described in the first aspect of the present invention; the color developing reagent comprises hydrogen peroxide and a color developing substrate; the color developing substrate comprises at least one of 3,3',5,5'-tetramethylbenzidine (TMB), 2,2'-diazobis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt, o-phenylenediamine, 3,3'-diaminobenzidine, 4-chloro-1-naphthol, and 3-amino-9-ethylcarbazole.
[0067] In some embodiments of the present invention, the kit is a mercury ion detection kit.
[0068] In some embodiments of the present invention, the kit is a kit for detecting mercury ions in a digestion solution.
[0069] In some embodiments of the present invention, the digestion solution is a neutralized high-acid, high-salt, strong oxidizing digestion solution.
[0070] In some specific embodiments of the present invention, the digestion solution includes a nitric acid digestion solution.
[0071] In some examples of the present invention, the nitric acid digestion solution includes a food nitric acid digestion solution and / or a medicinal material nitric acid digestion solution.
[0072] Specifically, the medicinal materials can be Chinese medicinal materials.
[0073] In some embodiments of the present invention, the concentration of the chromogenic substrate is 1 to 10 mol / L; the amount of the chromogenic substrate in the kit is 200 to 400 μL.
[0074] In some embodiments of the present invention, the mass fraction of the hydrogen peroxide is 15-30%; the amount of hydrogen peroxide in the kit is 100-300 μL.
[0075] In some embodiments of the present invention, the peroxidase-like material is prepared into a solution using anhydrous ethanol, and the concentration is 1-4 mg / mL; the amount of the peroxidase-like material solution in the kit is 50-100 μL.
[0076] The fourth aspect of the present invention provides a method for detecting mercury ions, using the peroxidase-like material described in the first aspect of the present invention or the kit described in the third aspect of the present invention for detection.
[0077] In some embodiments of the present invention, the steps include: taking a sample solution to be tested, a color developing substrate, hydrogen peroxide and a peroxidase-like material, and testing the absorbance of the solution after mixing;
[0078] The sample solution to be tested includes at least one of a nitric acid digestion solution of food, a nitric acid digestion solution of medicinal materials, and mercury-containing wastewater; the chromogenic substrate includes hydrogen peroxide and a chromogenic substrate; the chromogenic substrate includes at least one of 3,3',5,5'-tetramethylbenzidine, 2,2'-azobis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt, o-phenylenediamine, 3,3'-diaminobenzidine, 4-chloro-1-naphthol, and 3-amino-9-ethylcarbazole.
[0079] In some embodiments of the present invention, the concentration of the chromogenic substrate is 1-10 mol / L; the amount of the chromogenic substrate in the kit is 200-400 μL.
[0080] In some embodiments of the present invention, the mass fraction of the hydrogen peroxide is 15-30%; the amount of hydrogen peroxide in the kit is 100-300 μL.
[0081] In some embodiments of the present invention, the peroxidase-like material is prepared into a solution using anhydrous ethanol with a concentration of 1 to 4 mg / mL; the amount of the peroxidase-like material solution in the kit is 50 to 100 μL.
[0082] In some embodiments of the present invention, the color developing substrate, hydrogen peroxide, and peroxidase-like material are mixed with the sample to be tested, and then allowed to stand for 10 to 50 minutes, and the absorbance is tested.
[0083] In some embodiments of the present invention, the absorbance test is the absorbance test at 600 nm.
[0084] Compared with the prior art, the present invention has at least the following beneficial technical effects:
[0085] (1) The peroxidase-like material provided by the present invention adopts a two-dimensional nanomaterial with excellent specific surface area as a carrier, uses a polymer with a large molecular weight as a stabilizer to wrap a nano-precious metal, and loads it on the wrinkled two-dimensional nanomaterial. It has peroxidase-like activity, and its catalytic activity in nitric acid digestion solution not only does not decrease, but is enhanced. Moreover, the activity is affected by the concentration of trace mercury ions. In the presence of hydrogen peroxide and a chromogenic substrate, it can complete the rapid, sensitive and specific quantification of mercury ions in only 10 minutes, and has the advantages of high detection sensitivity, low detection limit and short detection time.
[0086] (2) The peroxidase-like material of the present invention has the characteristics of high detection sensitivity, low detection limit, and short detection time, and the catalytic activity can be enhanced in the digestion solution. By using this type of peroxidase material in combination with a colorimetric reagent, a kit can be prepared for the detection of mercury ions.
[0087] (3) The method for detecting mercury ions provided by the present invention uses the peroxidase-like material of the present invention or a kit containing such peroxidase material for detection, specifically detecting mercury ions by colorimetry, which has simple steps and low cost, and can be semi-quantitatively detected by the naked eye. In addition, using the digestion solution as the detection matrix, the measured mercury content is consistent with the actual content in the sample, and is consistent with the results of the standard method (i.e., inductively coupled plasma mass spectrometry), and the detection limit is lower than the limit of the Chinese Pharmacopoeia (2020 edition). BRIEF DESCRIPTION OF THE DRAWINGS
[0088] Figure 1 The results of the AuNPs@cGO detection of mercury ions in the digestion solution in Example 1 are shown in FIG. Figure 1 (a) is the UV absorption spectrum of TMB / H2O2 catalyzed color development in digestion solutions containing different mercury ion concentrations. Figure 1 (b) is the linear fitting curve of mercury ion concentration and absorbance.
[0089] Figure 2 The SEM images of AuNPs@cGO synthesized in Examples 1 to 4 are shown in FIG. Figure 2 (a) to (d) respectively represent the SEM images of AuNPs@cGO of Example 4, Example 3, Example 2 and Example 1.
[0090] Figure 3 The figure is a comparison of the absorbance of different anions and cations when AuNPs@cGO in Example 2 catalyzes TMB / H2O2 color development in the digestion solution; wherein, Figure 3 (a) is the absorbance comparison of mercury ions or other ions. Figure 3 (b) is the absorbance comparison of the co-existence of mercury ions and one other ion.
[0091] Figure 4 The ultraviolet spectrum of the peroxidase-like material in Example 5 catalyzing TMB / H2O2 color development; wherein, Figure 4 The test matrix of (a) is water, Figure 4 The detection matrix of (b) is the digestion solution.
[0092] Figure 5 It is the double reciprocal graph of AuNPs@cGO of Example 5 based on Lineweaver-Burk equation; wherein, Figure 5 The test matrix of (a) is water, Figure 5 The detection matrix of (b) is the digestion solution.
[0093] Figure 6 The performance characterization comparison of AuNPs@cGO and cit, xyl&cit, and GO in Examples 1 to 5 is shown; wherein, Figure 6 (a) is the multiple of absorbance enhancement of AuNPs@cGO and cit, xyl&cit, and GO in Examples 1 to 5 when detecting mercury ions in the digestion solution, Figure 6 (b) is the particle size of AuNPs@cGO in Examples 1 to 5. DETAILED DESCRIPTION
[0094] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0095] The following describes in detail different embodiments.
[0096] Example 1
[0097] A peroxidase-like material comprises graphene oxide, nano-gold and xylan; the nano-gold is wrapped in xylan and loaded on the wrinkled graphene oxide; the peroxidase-like material is in the shape of a wrinkled paper ball, and the particle size is 1063nm; and the preparation method thereof is as follows:
[0098] S1. Pour 23 mL of concentrated sulfuric acid into a beaker and place it in a refrigerator to cool. Add 1 g of graphite and 0.5 g of sodium nitrate under ice bath conditions, stir at 100 rpm for 5 min, then slowly add 3 g of potassium permanganate several times, react at low temperature (<20°C) for 30 min, then heat up for medium temperature reaction (35°C, 90 min), and finally slowly add 46 mL of water continuously, control the temperature to <100°C, and react for 30 min; after the reaction, add 140 mL of water, cool to room temperature, add 10 mL of 30% H2O2, centrifuge at 3000 rpm for 10 min to remove the supernatant, use 10% HCl to centrifuge and wash the precipitate 3 times (3000 rpm, 10 min), then use water to centrifuge and wash until the supernatant is neutral (10000 rpm, 10 min), and disperse the precipitate in water to obtain a GO solution;
[0099] S2. 2.381 mL of the 2.1 mg / mL GO solution obtained in step S1 was dispersed in 44 mL of water by ultrasound (150 W, 3 min), 0.25 mL of 50 mmol / L chloroauric acid was added, and the mixture was heated to boiling while stirring (400 rpm), and then 3 mL of 0.05 g / mL xylan solution (solvent: dimethyl sulfoxide) and 0.3 mL of 500 mmol / L sodium citrate solution were added dropwise to obtain a mixture, and the mixture was reacted for 15 min to obtain an AuNPs / GO (enzyme material precursor) solution;
[0100] The concentration of GO in the mixture was 0.05 mg / mL, the concentration of chloroauric acid was 0.25 mmol / L, the concentration of xylan was 3 mg / mL, and the concentration of sodium citrate was 3 mmol / L;
[0101] S3. After heating 100 mL of olive oil to 160°C, add 10 mL of the AuNPs / GO solution obtained in step S2 dropwise, and stir using a homogenizer (3500 rpm) and a magnetic stirrer (400 rpm). After there are no bubbles, cool to room temperature and centrifuge. Wash repeatedly with ethanol to obtain AuNPs@cGO (peroxidase-like material), and redisperse in 10 mL of ethanol for later use. The concentration of AuNPs@cGO is 2.7 mg / mL.
[0102] The SEM image of the peroxidase-like material of this example is as follows Figure 2 As shown in (d), due to the low GO concentration, only a part of it is wrinkled into a sphere, while the other part is only slightly folded.
[0103] The mercury ion detection effect of the peroxidase-like material of this embodiment was tested as follows:
[0104] 0.5 g of white lotus seed powder was dispersed in 5 mL of nitric acid overnight, and the digestion solution was obtained after microwave digestion. The solution was neutralized and fixed to 25 mL. After drying 5 mL of the digestion solution, the salt concentration was measured to be 162.5 mg / mL. 50 μL of Hg 2+ , 330 μL 10 mmol / L TMB (3,3',5,5'-tetramethylbenzidine), 210 μL 30% H2O2, 75 μL AuNPs@cGO, mix well, let stand for 10 min, and measure the UV absorption spectrum of the solution. Figure 1 As shown in (a), as the mercury ion concentration increases, the absorbance at 600 nm (A600) increases, and the mercury ion concentration and A600 have a linear relationship in the range of 52.9 to 997 nmol / L ( Figure 1 (b)), the detection limit was 5.89nmol / L.
[0105] Example 2
[0106] A peroxidase-like material comprises graphene oxide, nano-gold and xylan; the xylan encapsulates the nano-gold and loads it on the graphene oxide; the peroxidase-like material is in the shape of a crumpled paper ball, and has a particle size of 1762 nm; and the preparation method thereof is as follows:
[0107] S1. Pour 11.5 mL of concentrated sulfuric acid into a beaker and place it in a refrigerator to cool. Add 0.5 g of graphite and 0.25 g of sodium nitrate under ice bath conditions, stir at 200 rpm for 10 min, then slowly add 1.5 g of potassium permanganate several times, react at low temperature (<20°C) for 20 min, then heat up for medium temperature reaction (35°C, 70 min), and finally slowly add 23 mL of water continuously, control the temperature to <100°C, and react for 20 min; after the reaction, add 70 mL of water, cool to room temperature, add 5 mL of 30% H2O2 by mass, centrifuge (4000 rpm, 5 min) to remove the supernatant, use 10% HCl to centrifuge and wash the precipitate 4 times (4000 rpm, 5 min), then use water to centrifuge and wash until the supernatant is neutral (13000 rpm, 10 min), and disperse the precipitate in water to obtain GO solution;
[0108] S2. 4.762 mL of the 2.1 mg / mL GO solution obtained in step S1 was dispersed in 38 mL of water by ultrasound (150 W, 3 min), 0.5 mL of 50 mmol / L chloroauric acid was added, and the mixture was heated to boiling while stirring (300 rpm), and 6 mL of 0.05 g / mL xylan solution (solvent: dimethyl sulfoxide) and 0.6 mL of 500 mmol / L sodium citrate solution were added dropwise to obtain a mixture, and the mixture was reacted for 20 min to obtain AuNPs / GO (enzyme material precursor);
[0109] The concentration of GO in the mixture was 0.2 mg / mL, the concentration of chloroauric acid was 0.5 mmol / L, the concentration of xylan was 6 mg / mL, and the concentration of sodium citrate was 6 mmol / L;
[0110] S3. After heating 200 mL of olive oil to 140°C, add 5 mL of the AuNPs / GO solution obtained in step S2 dropwise, and stir using a homogenizer (1000 rpm) and a magnetic stirrer (300 rpm). After there are no bubbles, cool to room temperature and centrifuge. Wash repeatedly with ethanol to obtain AuNPs@cGO (peroxidase-like material), and redisperse in 5 mL of ethanol for later use. The concentration of AuNPs@cGO is 2.1 mg / mL.
[0111] The peroxidase-like material of this embodiment was characterized, and the results are as follows Figure 2 As shown in (c), from its SEM image, it can be seen that the original lamellar two-dimensional graphene curled up and shrunk into particles, and the large number of wrinkles on the surface increased the surface area and catalytic active sites.
[0112] The mercury ion detection effect of the peroxidase-like material of this embodiment was tested as follows:
[0113] 0.5 g of white lotus seed powder was dispersed in 5 mL of nitric acid overnight, and the digestion solution was obtained after microwave digestion, neutralized and fixed to 25 mL. KCl, Ca(NO3)2, Mg(NO3)2, Al(NO3)2, FeCl3, Co(NO3)2, Ni(NO3)2, Zn(NO3)2, MnCl2, Ba(NO3)2, Cr(NO3)3, Cu(NO3)2, Pb(NO3)2, Cd(NO3)2, NaSO4, NaHPO4, NaCl, and HgSO4 were used as K + , Ca 2+ Mg 2+ 、Al 3+ , Fe 3+ 、Co 3+ 、Ni 2+ 、Zn 2+ , Mn 2+ , Ba 2+ Cr 3+ , Cu 2+ , Pb 2+ 、Cd 2+ 、SO4 2- 、HPO4 2- , Cl - , Hg 2+The ion source was 1.32 μmol / L, and the ion concentration was 1.32 μmol / L. The effects of common anions and cations on the color development of AuNPs@cGO catalyzed by TMB / H2O2 in the digestion solution were evaluated. The results are shown in Figure 3 shown. Figure 3 In (a), compared with the blank (BLANK), when 1.32μmol / L mercury ions were present, the absorbance increased from 0.289 to 2.338. When other common anions and cations were present, no such significant increase in absorbance was observed. Compared with the 708% increase caused by adding the same concentration of mercury ions, the increase was very small. When mercury ions and another ion were present in the solution at the same time ( Figure 3 (b)), and the absorbance did not change significantly. Figure 3 In (b), “or H2O” means that only Hg 2+ , no second ion was added.
[0114] Example 3
[0115] A peroxidase-like material comprises graphene oxide, nano-gold and xylan; the nano-gold is wrapped in xylan and loaded on the graphene oxide; the peroxidase-like material is in the shape of a crumpled paper ball, and the particle size is 2026nm; and the preparation method thereof is as follows:
[0116] S1. Pour 6 mL of concentrated sulfuric acid into a beaker and place it in a refrigerator to cool. Add 0.25 g of graphite and 0.125 g of sodium nitrate under ice bath conditions, stir at 100 rpm for 10 min, then slowly add 0.75 g of potassium permanganate several times, react at low temperature (<20°C) for 25 min, then heat up for medium temperature reaction (35°C, 80 min), finally add 12 mL of water slowly and continuously, control the temperature to <100°C, and react for 25 min; after the reaction, add 35 mL of water, wait until it cools to room temperature, add 2.5 mL of 30% H2O2, centrifuge (3500 rpm, 5 min) to remove the supernatant, use 10% HCl to centrifuge and wash the precipitate 4 times (35000 rpm, 5 min), then use water to centrifuge and wash until the supernatant is neutral (14000 rpm, 5 min), disperse the precipitate in water to obtain GO solution;
[0117] S2. 9.524 mL of the 2.1 mg / mL GO solution obtained in step S1 was dispersed in 35 mL of water by ultrasound (150 W, 6 min), 0.3 mL of 50 mmol / L chloroauric acid was added, and the mixture was heated to boiling while stirring (400 rpm), and then 5 mL of 0.05 g / mL xylan solution (solvent: dimethyl sulfoxide) and 0.5 mL of 500 mmol / L sodium citrate solution were added dropwise to obtain a mixture, and the mixture was reacted for 25 min to obtain AuNPs / GO (enzyme material precursor);
[0118] The concentration of GO in the mixture was 0.4 mg / mL, the concentration of chloroauric acid was 0.3 mmol / L, the concentration of xylan was 5 mg / mL, and the concentration of sodium citrate was 5 mmol / L;
[0119] S3. After heating 50 mL of olive oil to 180°C, add 15 mL of AuNPs / GO solution dropwise, and stir with a homogenizer (3000 rpm) and a magnetic stirrer (500 rpm). After there are no bubbles, cool to room temperature and centrifuge. Wash repeatedly with ethanol to obtain AuNPs@cGO (peroxidase-like material), and redisperse in 15 mL of ethanol for later use. The concentration of AuNPs@cGO is 1.2 mg / mL.
[0120] The SEM image of the peroxidase-like material obtained in this example is as follows Figure 2 As shown in (b), it appears as a crumpled paper ball with a large number of wrinkles on the surface.
[0121] Example 4
[0122] A peroxidase-like material comprises graphene oxide, nano-gold and xylan; the xylan encapsulates the nano-gold and loads it on the graphene oxide; the peroxidase-like material is in the shape of a crumpled paper ball, and has a particle size of 2713 nm; and the preparation method thereof is as follows:
[0123] S1. Pour 17 mL of concentrated sulfuric acid into a beaker and place it in a refrigerator to cool. Add 0.75 g of graphite and 0.375 g of sodium nitrate under ice bath conditions, stir at 100 rpm for 10 min, then slowly add 2.25 g of potassium permanganate several times, react at low temperature (<20°C) for 30 min, then heat up for medium temperature reaction (35°C, 90 min), finally slowly add 34.5 mL of water continuously, control the temperature to <100°C, and react for 30 min; after the reaction, add 105 mL of water, wait until it cools to room temperature, add 7.5 mL of 30% H2O2 by mass, centrifuge (3000 rpm, 10 min) to remove the supernatant, use 10% HCl to centrifuge and wash the precipitate 3 times (3000 rpm, 10 min), then use water to centrifuge and wash until the supernatant is neutral (10000 rpm, 10 min), disperse the precipitate in water to obtain GO solution;
[0124] S2. 19.048 mL of the 2.1 mg / mL GO solution obtained in step S1 was dispersed in 19 mL of water by ultrasound (150 W, 4 min), 1 mL of 50 mmol / L chloroauric acid was added, and the mixture was heated to boiling while stirring (300 rpm), and then 10 mL of 0.05 g / mL xylan solution (solvent: dimethyl sulfoxide) and 1 mL of 500 mmol / L sodium citrate solution were added dropwise to obtain a mixture, and the mixture was reacted for 35 min to obtain AuNPs / GO (enzyme material precursor);
[0125] The concentration of GO in the mixture was 0.8 mg / mL, the concentration of chloroauric acid was 1 mmol / L, the concentration of xylan was 10 mg / mL, and the concentration of sodium citrate was 10 mmol / L;
[0126] S3. After heating 100 mL of olive oil to 160°C, add 20 mL of AuNPs / GO solution dropwise, and stir with a homogenizer (2000 rpm) and a magnetic stirrer (400 rpm). After there are no bubbles, cool to room temperature and centrifuge. Wash repeatedly with ethanol to obtain AuNPs@cGO (peroxidase-like material), and redisperse in 20 mL of ethanol for later use. The concentration of AuNPs@cGO is 2.2 mg / mL.
[0127] The SEM image of the peroxidase-like material of this example is as follows Figure 2 As shown in (a), it appears as a crumpled paper ball with a large number of wrinkles on the surface.
[0128] Example 5
[0129] A peroxidase-like material comprises graphene oxide, nano-gold and xylan; the xylan encapsulates the nano-gold and loads it on the graphene oxide; the peroxidase-like material is in the shape of a crumpled paper ball, and has a particle size of 1590 nm; and the preparation method thereof is as follows:
[0130] S1. Pour 18.4 mL of concentrated sulfuric acid into a beaker and place it in a refrigerator to cool. Add 0.8 g of graphite and 0.4 g of sodium nitrate under ice bath conditions, stir at 100 rpm for 5 min, then slowly add 2.4 g of potassium permanganate several times, react at low temperature (<20°C) for 30 min, then heat up for medium temperature reaction (35°C, 90 min), and finally slowly add 36.8 mL of water continuously, control the temperature to <100°C, and react for 30 min; after the reaction, add 112 mL of water, wait until it cools to room temperature, add 8 mL of 30% H2O2 by mass, centrifuge (3000 rpm, 10 min) to remove the supernatant, use 10% HCl to centrifuge and wash the precipitate 3 times (3000 rpm, 10 min), then use water to centrifuge and wash until the supernatant is neutral (10000 rpm, 10 min), and disperse the precipitate in water to obtain a GO solution;
[0131] S2. 1.191 mL of the 2.1 mg / mL GO solution obtained in step S1 was dispersed in 45 mL of water by ultrasound (150 W, 4 min), 0.25 mL of 50 mmol / L chloroauric acid was added, and the mixture was heated to boiling while stirring (400 rpm), and then 3 mL of 0.05 g / mL xylan solution (solvent: dimethyl sulfoxide) and 0.3 mL of 500 mmol / L sodium citrate solution were added dropwise to obtain a mixture, and the mixture was reacted for 15 min to obtain AuNPs / GO (enzyme material precursor);
[0132] The concentration of GO in the mixture was 0.1 mg / mL, the concentration of chloroauric acid was 1 mmol / L, the concentration of xylan was 3 mg / mL, and the concentration of sodium citrate was 3 mmol / L;
[0133] S3. After heating 200 mL of olive oil to 160°C, add 50 mL of AuNPs / GO solution dropwise, and stir with a homogenizer (3500 rpm) and a magnetic stirrer (400 rpm). After there are no bubbles, cool to room temperature and centrifuge. Wash repeatedly with ethanol to obtain AuNPs@cGO (peroxidase-like material), and redisperse in 50 mL of ethanol for later use. The concentration of AuNPs@cGO is 2.9 mg / mL.
[0134] The same method as in this example was used, but without adding GO and shrinking, to prepare a nano-gold Au-xyl-cit solution reduced by xylan and sodium citrate; without adding GO and xylan, and shrinking, to prepare a nano-gold Au-cit solution reduced by sodium citrate; the performance differences of the AuNPs / GO solution and AuNPs@cGO solution of this example, the Au-xyl-cit solution, and the Au-cit solution were compared, and the results are as follows: Figure 4 The details are as follows:
[0135] 0.5g of white lotus seed powder was dispersed in 5mL of nitric acid overnight, and after microwave digestion, it was neutralized and fixed to 25mL to obtain the digestion solution for testing. Using water as a control, the effect of the digestion solution on the catalytic performance of the four enzyme materials (Au-cit, Au-xyl-cit, AuNPs / GO and AuNPs@cGO) solutions was measured: 290μL of digestion solution or water was added with 50μL of 9μmol / L Hg 2+ , 330μL 10mmol / L TMB, 210μL 30% H2O2, and 75μL enzyme material solution (Au-cit, Au-xyl-cit, AuNPs / GO or AuNPs@cGO), mixed evenly, the mercury ion concentration in the system was 1.32μmol / L, let it stand for 10min, and measure the UV absorption spectrum of the solution. Figure 4As shown, in water ( Figure 4 (a) Compared with Au-cit, the color of Au-xyl-cit catalytic color development is darker, indicating that the additional addition of xylan in the process of synthesizing nanogold improves the catalytic effect. The loading of Au-xyl-cit on GO and the shrinking of AuNPs / GO from sheet to granule both reduce the exposure of Au-xyl-cit surface active sites, which weakens the catalytic effect and leads to a decrease in absorbance. When the catalytic environment is changed from water to digestion solution ( Figure 4 (b) The absorption peak blue-shifted from 650nm to 600nm, and the absorbance weakened due to the aggregation of gold nanoparticles and the decrease of catalytic activity caused by the high concentration of salt solution. The presence of graphene oxide, especially the wrinkled paper ball-like structure of peroxidase-like materials, increased the absorbance of the solution after AuNPs@cGO catalysis from 0.37 to 2.60, which was greatly enhanced, indicating that its catalytic performance in high-salt digestion solution was greatly improved.
[0136] In order to compare the AuNPs@cGO in water and digestion solution (preparation method see Figure 4 The catalytic activity of AuNPs@cGO was analyzed by using the Michaelis-Menten model. The kinetics of AuNPs@cGO catalyzing TMB / H2O2 color development was studied. The results showed that the AuNPs@cGO catalyzed TMB / H2O2 color development was catalyzed by mixing 290 μL water or digestion solution and 50 μL 9 μmol / L Hg 2+ , 210μL 30% H2O2 by mass, 330μL TMB of different concentrations and 75μL AuNPs@cGO solution of Example 5, the absorbance change within 10 minutes, and the double reciprocal graph is made by Lineweaver-Burk equation. Among them, when testing the catalytic kinetics in water, the concentrations of TMB are 1mmol / L, 2.5mmol / L, 5mmol / L and 7.5mmol / L respectively; when testing the kinetics in the digestion solution, the concentrations of TMB are 1mmol / L, 1.5mmol / L, 2mmol / L, 2.5mmol / L and 5mmol / L respectively. Figure 5 As shown in Figure 2, the maximum reaction rate Vmax of AuNPs@cGO in water is 8.65×10 -7 M / min, the Michaelis constant Km was 0.586mM, and the maximum reaction rate Vmax in the digestion solution increased by 22.5 times to 1.95×10 -5 The Michaelis constant Km was 2.41 mM, indicating that the catalytic rate in the digestate was much greater than that in water. The increase in the Michaelis constant may be due to the salt ions in the digestate occupying part of the catalytic active sites, which reduced their affinity with TMB.
[0137] For the peroxidase-like materials of Examples 1 to 5, in order to verify the role of xylan and GO in the synthesis, three groups of enzyme materials were set up in the same way as in Example 5. The differences from Example 5 are as follows: (1) only sodium citrate was used without adding xylan and GO, and the product obtained was recorded as cit; (2) only xylan and sodium citrate were used without adding GO, and the product obtained was recorded as xyl&cit; (3) xylan, sodium citrate and GO were used without shrinking (i.e., step S3 was omitted), and the product obtained was recorded as GO. The peroxidase-like materials in Examples 1 to 5 are Figure 6 The horizontal axis of is respectively represented by the GO concentration in the mixture of step S2. The performance characterization analysis of the peroxidase-like materials and cit, xyl&cit, and GO of Examples 1 to 5 is as follows:
[0138] The results of cit, xyl&cit and GO in the presence of 1.32 μmol / L Hg were respectively determined. 2+ Digestion solution (preparation method see Figure 4 The absorbance enhancement factor ((A-A0) / A0) compared with the blank when the TMB / H2O2 was catalyzed to develop color for 10 minutes in the analysis was used as a parameter to measure the detection sensitivity. Figure 6 As shown in (a), after adding xylan, the sensitivity of the synthesized gold nanoparticles increased from 2.27 to 2.84, and the absorbance range (A-A0) also increased from 0.098 to 0.226. This is because the molecular chain of xylan has a good protective effect on the gold nanoparticles in the high salt concentration environment of the digestion solution. When GO is added but not wrinkled, the obtained material only has the wrinkled structure of GO itself, which is still a two-dimensional material. It does not shrink to form paper ball-like particles. Its sensitivity slightly decreases to 2.28, and the absorbance range decreases to 0.166.
[0139] Combination Figure 6 (a) and Figure 6 (b) In order to verify the effect of different GO concentrations on the particle size and detection sensitivity of AuNPs@cGO during the synthesis, the AuNPs@cGO of Examples 1 to 5 were measured in a solution containing 1.32 μmol / L Hg 2+ Digestion solution (preparation method see Figure 4 The multiple of absorbance enhancement compared with the blank when catalyzing TMB / H2O2 color development in the analysis. Figure 6 (a) and Figure 6 As shown in (b), the concentration of GO controls the particle size of AuNPs@cGO. As its concentration decreases from 0.8 mg / mL to 0.1 mg / mL, the particle size of AuNPs@cGO decreases from 2714 nm to 1036 nm. 2+The sensitivity of the detection also increased from 1.67 (GO concentration 0.8 mg / mL) to 9.67 (GO concentration 0.1 mg / mL), which is mainly due to the increase in specific surface area, which gives the peroxidase-like material more catalytic active sites. When the GO concentration continued to decrease from 0.1 mg / mL to 0.05 mg / mL, although the particle size also decreased from 1762 nm to 1590 nm, the detection sensitivity did not increase further but decreased. This may be because when the GO concentration is too low, there is not enough GO to shrink into a sphere, and there is only limited shrinkage ( Figure 2 (d)) Such a structure does not solve the defect that graphene two-dimensional sheets are easy to restack, and the active catalytic sites are easily masked, resulting in reduced detection sensitivity.
[0140] In summary, the present invention aims at the characteristic that the high-concentration salt solution of the digestion solution easily inactivates the nanoparticles, and successfully prepares a new type of peroxidase-like material by polymer encapsulation, two-dimensional nanomaterial loading, and two-dimensional sheet shrinkage granulation. Due to the stabilizing effect of polymer encapsulation, the peroxidase-like material uses the two-dimensional nanomaterial as a carrier of nanogold and is wrinkled to form a wrinkled paper ball-like peroxidase-like material. The peroxidase-like material has enhanced peroxidase-like activity in the digestion solution, and the activity of the peroxidase-like material is not affected by the presence of Hg. 2+ When very weak, and with Hg 2+ After forming gold-mercury alloy, it will be greatly enhanced and can be used for the detection of mercury ions in medicinal materials and foods after extraction through the required standard digestion procedures.
[0141] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A peroxidase-like material, characterized in that: It comprises two-dimensional nanomaterials, nano noble metals and polymers; the polymers wrap the nano noble metals and are loaded on the two-dimensional nanomaterials; and the two-dimensional nanomaterials have a wrinkled morphology.
2. The peroxidase-like material according to claim 1, characterized in that: The peroxidase-like material is in the shape of a crumpled paper ball; And / or, the particle size of the peroxidase-like material is 0.1-10 μm.
3. The peroxidase-like material according to claim 1, characterized in that: In the peroxidase-like material, the mass ratio of the nano noble metal to the polymer is (0.01-0.2):1; And / or, in the peroxidase-like material, the mass ratio of the two-dimensional nanomaterial to the polymer is (0.01-0.4):
1.
4. The peroxidase-like material according to claim 1, characterized in that: The two-dimensional nanomaterial includes at least one of graphene oxide and Mxene; And / or, the polymer includes at least one of xylan, chitosan, polyethylene glycol, and polyethyleneimine; And / or, the nano noble metal includes at least one of gold, silver, platinum and palladium.
5. A method for preparing the peroxidase-like material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The two-dimensional nanomaterial, the noble metal precursor and the polymer are mixed to form a mixture, and the enzyme material precursor is obtained by reaction; The enzyme material precursor is mixed with an oil phase to react and obtain the peroxidase-like material.
6. The preparation method according to claim 5, characterized in that: The mixture also includes a reducing agent; the reducing agent includes at least one of sodium citrate, ascorbic acid, and sodium borohydride; And / or, the noble metal precursor includes at least one of chloroauric acid, silver nitrate, chloroplatinic acid, and chloropalladic acid; And / or, the oil phase comprises at least one of plant oil and mineral oil.
7. The preparation method according to claim 6, characterized in that: The two-dimensional nanomaterial and the noble metal precursor are dispersed in water, heated to boiling, and then a reducing agent and a polymer are added to react to obtain the enzyme material precursor; And / or, the reaction time of the mixture is 10 to 50 minutes; And / or, the temperature of the oil phase is 130-190°C.
8. A kit, characterized in that: The invention comprises a peroxidase-like material and a color developing reagent; the peroxidase-like material is the peroxidase-like material according to any one of claims 1 to 4; the color developing reagent comprises hydrogen peroxide and a color developing substrate; the color developing substrate comprises at least one of 3,3',5,5'-tetramethylbenzidine, 2,2'-azobis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt, o-phenylenediamine, 3,3'-diaminobenzidine, 4-chloro-1-naphthol and 3-amino-9-ethylcarbazole.
9. A method for detecting mercury ions, characterized in that: The detection is performed using the peroxidase-like material according to any one of claims 1 to 4 or the kit according to claim 8.
10. The detection method according to claim 9, characterized in that: The method comprises the following steps: taking a sample solution to be tested, a color developing substrate, hydrogen peroxide and a peroxidase-like material, and testing the absorbance of the solution after mixing; The sample solution to be tested includes at least one of a nitric acid digestion solution of food, a nitric acid digestion solution of medicinal materials, and mercury-containing wastewater; the chromogenic substrate includes hydrogen peroxide and a chromogenic substrate; the chromogenic substrate includes at least one of 3,3',5,5'-tetramethylbenzidine, 2,2'-azobis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt, o-phenylenediamine, 3,3'-diaminobenzidine, 4-chloro-1-naphthol, and 3-amino-9-ethylcarbazole.